A Reflection on the Theory of God’s Inferred (Attained) Knowledge of Pre-Creation Creatures - Ebrahim Rostami (آموزه‌‌های فلسفه اسلامي)
In this research, the views of Professor Fayyazi have been analyzed. Sadr-ol-Mote'allehin, according to the rule of indivisible entity and by proving the existential perfections of possible beings in the essence of the Almighty Supreme Being, explaining the knowledge by presence of God (immediate apprehension, intuitive knowledge) in the position of essence. Professor Fayyazi believes that this view has its drawbacks. The basic drawback is that Mulla Sadrā’s interpretation of the systematic ambiguity of existence becomes contradictory and the structural drawback with this, is that, this view is incapable of proving God’s knowledge of the contingent things which annihilated (nonexistent) and the impossibilities. After explaining the conceptual, systematic ambiguity and individual (particular) unity of existence, the author has reached the conclusion that the above-mentioned basic drawback has not been included Ṣadr-ol-Mote'allehin’s argument on the immediate apprehension of God is based on the systematic ambiguity unity of existence, while the basic drawback which is related to individual oneness (particular unity) unity is still existed and for the structural problems, it has been stated that although the proof of this kind of immediate apprehension for God has methodological weaknesses, but the final opinion of Ṣadr-ol-Mote'allehin is the same synoptic (collective) knowledge while discovering (unveiling) in detail what is immediate apprehension and then the theory of Professor Fayyazi about the inferred knowledge (attained knowledge) of God to the creatures before creation has been examined.